2021
DOI: 10.1101/2021.11.02.21265801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expanding the Russian allele frequency reference via cross-laboratory data integration: insights from 7,452 exome samples

Abstract: The frequency of a genetic variant in a population is crucially important for accurate interpretation of known and novel variant effects in medical genetics. Recently, several large allele frequency databases, such as Genome Aggregation Database (gnomAD), have been created to serve as a global reference for such studies. However, frequencies of many rare alleles vary dramatically between populations, and population-specific allele frequency can be more informative than the global one. Many countries and region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…In general, our data agree with previously published studies where differences between the Russian and European populations were shown for some rare variants [ 9 , 10 ]. It was shown previously that CFTRdele2,3 variant (hg19::chr7:117138367-117159446del) has Slavic origin with the highest frequency among CF patients of 6.4% in Czechia (5.8% in Russia) [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In general, our data agree with previously published studies where differences between the Russian and European populations were shown for some rare variants [ 9 , 10 ]. It was shown previously that CFTRdele2,3 variant (hg19::chr7:117138367-117159446del) has Slavic origin with the highest frequency among CF patients of 6.4% in Czechia (5.8% in Russia) [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we performed a comparison of the obtained AF with those from recently published data for the Russian population [ 6 , 10 ]. There were no statistically significant differences in AF between our results and these two population studies, which is consistent with a close ethnic composition of studied groups of samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, both in the patient and his sister, we found a variant in the FHOD3 gene (chr18:36652930 G>A) affecting the canonical donor splice site after exon 12 of cardiospecific isoform (NM_001281740.3: c.1646+1G>A). This variant was absent from the gnomAD population database as well as from the recently emerged open database of genetic variation in Russian population “RuSeq” [ 20 ], but it was recently reported by Semsarian et al [ 21 ] in their HCM study. It also had a ClinVar entry describing it as a variant of uncertain significance (VUS) [ 22 ] in HCM without further details.…”
Section: Resultsmentioning
confidence: 98%